Evaluation of the efficiency of the use of intellectual potential in the regions of Kazakhstan - R. K. Sagiyeva; A. S. Zhuparova; R. M. Ruzanov; G. G. Sagi (Экономика: стратегия и практика, 2020)
Problems of effective use of intellectual potential as the main source of new knowledge and a key asset in creating innovations and ensuring the competitiveness of an individual, company, region, country continue to be the focus of attention of modern economists - researchers. At the same time, a detailed analysis of the regional specifics of the use of intellectual potential, which is determined not only by their natural and geographical differentiation, but also by such factors as the level of socio-economic and infrastructural development, especially in terms of access to modern information technologies, attracts special interest; sectoral structure of the region’s economy; the level and quality of life of the population. Analysis of the literature and the specifics of the development of the intellectual potential of our country made it possible to form a system of indicators to assess the effectiveness of its use in the regions of Kazakhstan. In this study, we use the DEA methodology to assess the effectiveness of intellectual potential in 17 regions of Kazakhstan for 2009, 2014, 2019. The results obtained in the course of the study show that the measures taken by the government to develop education, science and innovation in different regions of the country have led to opposite results. In fact, it can be argued that the intellectual potential of the country, along with insufficient government measures, was used ineffectively, since Kazakhstan did not demonstrate significant innovative breakthroughs during the study period.